Introduction of the French version of the Multidimensional Orientation Toward Dying and Death Inventory (MODDI-F/fre) - Wittkowski, Joachim; Paré, Pierre-Marc (Death Studies, 2022)
Research on death-related attitudes needs complex assessment instruments for multicultural contexts. The French version of the Multidimensional Orientation Toward Dying and Death Inventory was factor analytically constructed with data from Europe and Canada (N = 370). The 24-item instrument with five and three scales in the fear and acceptance domain, respectively, shows favorable psychometric properties. The influence of social desirability is negligible. Women tended to express stronger fears and weaker acceptance of dying and death. Gender differences emerged concerning Fear of One’s Own Dying and Fear of Corpses, with women scoring higher than men on both dimensions. The importance of assessing attitudes toward dying and death transdiagnostically is outlined.
CRIS-Team Scopus Importer:2022-08-26